Simulation of childbirth improves clinical management capacity and self-confidence in medical students. (2nd March 2018) - Mannella, Paolo; Antonelli, Rachele; Montt-Guevara, María Magdalena; Caretto, Marta; Palla, Giulia; Giannini, Andrea; Pancetti, Federica; Cuttano, Armando; Simoncini, Tommaso
Abstract : Background The learning process of physiological mechanisms of childbirth and its management are important elements in the education of medical students. In this study, we verify how the use of a high-fidelity simulator of childbirth improves competence of students in this regard. Methods A total of 132 medical students were recruited for the study in order to attend a physiological childbirth in a no-hospital environment after being assigned to two groups. The control group received only a normal cycle of lectures, while the simulation (SIM) group followed a specific training session on the simulator. Subsequently, both groups were assessed for their technical and non-technical skills in a simulated childbirth. Also, a self-assessment test regarding their self-confidence was administrated before and after simulation, and repeated after 8 weeks. Results The SIM group showed better performance in all the domains with a better comprehension of the mechanisms of childbirth, managing and assistance of labour and delivery. In addition, compared to the control group, they presented a better self-related awareness and self-assurance regarding the possibility of facing a birth by themselves. Conclusion The present study demonstrated that the use of a high-fidelity simulator for medical students allows a significant improvement in the acquisition of theoretical and technical expertise to assist a physiological birth.